1,2,3-Triazole derivatives as antitubercular agents: synthesis, biological evaluation and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Nawale, Laxman; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (MedChemComm, 2015)
Searching for new active molecules against Mycobacterium tuberculosis (MTB) H37Ra, a small focused library of 1,2,3-triazoles has been efficiently prepared via a click chemistry approach. The newly synthesized compounds were tested against drug-sensitive MTB. Several derivatives were found to be promising inhibitors of MTB characterized by lower MIC values (5.8-29.9 mu g mL(-1)). Among all the synthesized 31 compounds, 15e was the most active compound against MTB. Based on the results from the antitubercular activity, SAR for the synthesized series has been developed. The active compounds from the anti-tubercular study were further tested for anti-proliferative activity against THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity against these three cell lines except THP-1 at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antioxidant activities with an IC50 range of 10.1-37.3 mu g mL(-1). The molecular docking study of the synthesized compounds was performed against the DprE1 enzyme of MTB to understand the binding interactions. Moreover, the synthesized compounds were also analysed for ADME properties and all the experimental results promote us to consider this series as a starting point for the development of novel and more potent anti-tubercular agents in the future.

Facile synthesis of new N-sulfonamidyl-4-thiazolidinone derivatives and their biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Shingate, Bapurao B. (New Journal of Chemistry, 2016)
The one-pot three-component syntheses of new N-sulfonamide-thiazolidin-4-one derivatives were carried out in excellent yield using [HDBU][HSO4] as an ionic liquid under solvent-free conditions. The newly synthesized compounds were screened against fungal strains and a number of compounds were seen to display excellent antifungal activity. In addition, the synthesized compounds were screened for their scavenging activity of the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical and showed very good antioxidant activity. Finally, theoretical predictions derived from molecular docking studies against the potential target sterol 14 alpha-demethylase (CYP51) helped establish a link between the observed biological activity and the binding affinity, thereby providing insights into the specific bonding and non-bonding interactions governing the activity.

Novel tetrazoloquinoline-rhodanine conjugates: highly efficient synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG, a small focused library of rhodanine incorporated tetrazoloquinoline has been efficiently synthesized by using [HDBU][HSO4] acidic ionic liquid. The compound 3c found to be promising inhibitor of MTB H37Ra and M. bovis BCG characterized by lower MIC values 4.5 and 2.0 mu g/mL, respectively. The active compounds were further tested for cytotoxicity against HeLa, THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Again, the synthesized compounds were found to have potential antifungal activity. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target Zmp1 enzyme of MTB H37Ra, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of in vitro and in silico study suggest that these compounds possess ideal structural requirement for the further development of novel therapeutic agents. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Antitubercular; Cytotoxicity; Docking study; Rhodanine derivatives

Synthesis, biological evaluation and molecular docking of novel coumarin incorporated triazoles as antitubercular, antioxidant and antimicrobial agents - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Shingate, Bapurao B.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Nawale, Laxman; Sarkar, Dhiman; Navale, Govinda R.; Shinde, Sandip S. (Medicinal Chemistry Research, 2016)
A series of new coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular activity in vitro against Mycobacterium tuberculosis H37Ra, antioxidant activity by DPPH radical scavenging assay, antimicrobial activity in vitro against three gram-positive bacteria (Staphylococcus aureus, Micrococcus luteus and Bacillus cereus) and three gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens and Flavobacterium devorans as well as three fungi (Aspergillus niger, Penicillium chrysogenum and Curvularia lunata). The bioactive assay showed that some synthesized coumarin triazoles displayed comparable or even better antitubercular, antioxidant, antibacterial and antifungal efficacy in comparison with reference drugs. Furthermore, docking study has been performed against DprE1 enzyme of M. tuberculosis that showed good binding interactions. Moreover, the synthesized compounds were also analyzed for ADME properties and showed potential to build up as good oral drug candidates. New coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular, antioxidant, antibacterial and antifungal activity. Some of the coumarin-based triazole derivatives displayed comparable or even better efficacy in comparison with reference drugs. Molecular docking study has been performed against DprE1 enzyme of Mycobacterium tuberculosis showed good binding interactions. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Antitubercular; Click chemistry; Docking study

Ultrasound- and molecular sieves-assisted synthesis, molecular docking and antifungal evaluation of 5-(4-(benzyloxy)-substituted phenyl)-3-((phenylamino)methyl)-1,3,4-oxadiazole-2(3H)-thiones - Nimbalkar, Urja D.; Tupe, Santosh G.; Seijas Vazquez, Julio A.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nikalje, Anna Pratima G. (Molecules, 2016)
A novel series of 5-(4-(benzyloxy) substituted phenyl)-3-((phenyl amino) methyl)-1,3,4-oxadiazole-2(3H)-thione Mannich bases 6a-o were synthesized in good yield from the key compound 5-(4-(benzyloxy) phenyl)-1,3,4-oxadiazole-2(3H)-thione by aminomethylation with paraformaldehyde and substituted amines using molecular sieves and sonication as green chemistry tools. The antifungal activity of the new products was evaluated against seven human pathogenic fungal strains, namely, Candida albicans ATCC 24433, Candida albicans ATCC 10231, Candida glabrata NCYC 388, Cryptococcus neoformans ATCC 34664, Cryptococcus neoformans PRL 518, Aspergillus fumigatus NCIM 902 and Aspergillus niger ATCC 10578. The synthesized compounds 6d, 6f, 6g, 6h and 6j exhibited promising antifungal activity against the tested fungal pathogens. In molecular docking studies, derivatives 6c, 6f and 6i showed good binding at the active site of C. albicans cytochrome P450 enzyme lanosterol 14 alpha-demethylase. The in vitro antifungal activity results and docking studies indicated that the synthesized compounds have potential antifungal activity and can be further optimized as privileged scaffolds to design and develop potent antifungal drugs.
Keywords: 1; 3; 4-oxadiazoles; Antifungal activity; Mannich reaction; Molecular docking; Molecular sieves; Ultrasound

Quinolidene-rhodanine conjugates: facile synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Shingate, Bapurao B.; Nawale, Laxman; Sarkar, Dhiman; Khedkar, Vijay M.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N. (European Journal of Medicinal Chemistry, 2017)
A series of rhodanine incorporated quinoline derivatives were efficiently synthesized using reusable DBU acetate as ionic liquid and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) both in active and dormant state. Compounds 3e, 3f, 3g, 3h and 3i exhibited very good antitubercular activity. The active compounds were studied for cytotoxicity against HUVEC, THP-1, macrophages, A549, PANC-1 and HeLa cell lines using modified MTT assay and were found to be noncytotoxic. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity towards the MTB. Further, the synthesized compounds have been screened for their in vitro antifungal activity. In addition, the molecular docking studies revealed the binding modes of these compounds in active site of Zmp1 enzyme, which in turn helped to establish a structural basis of inhibition of mycobacteria. The results of present study clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug.

Synthesis of novel triazole-incorporated isatin derivatives as antifungal, antitubercular, and antioxidant agents and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nawale, Laxman; Arkile, Manisha A.; Sarkar, Dhiman; Shingate, Bapurao B. (Journal of Heterocyclic Chemistry, 2017)
A library of 1,2,3-triazoles efficiently prepared via click chemistry and evaluated for their antifungal, antitubercular, antioxidant, cytotoxicity, molecular docking and ADME prediction.

Novel benzylidenehydrazide-1,2,3-triazole conjugates as antitubercular agents: synthesis and molecular docking - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar; Nawale, Laxman; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash; Shingate, Bapurao B. (Mini Reviews in Medicinal Chemistry, 2018)
Novel 1,2,3-triazole based benzylidenehydrazide derivatives were synthesized and evaluated for antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra, M. bovis BCG and cytotoxic activity. Most of the derivatives exhibited promising in vitro potency against MTB characterized by lower MIC values. Among all the synthesized derivatives, compound 6a and 6j were the most active against active and dormant MTB H37Ra, respectively. Compound 6d was significantly active against dormant and active M. bovis BCG. The structure activity relationship has been explored on the basis of anti-tubercular activity data. The active compounds were also tested against THP-1, A549 and Panc-1 cell lines and showed no significant cytotoxicity. Further, the synthesized compounds were found to have potential antioxidant with IC50 range = 11.19-56.64 μg/mL. The molecular docking study of synthesized compounds was performed against DprE1 enzyme of MTB to understand the binding interactions. Moreover, synthesized compounds were also analysed for ADME properties and from all the experimental results, the potency of compounds indicate that, this series considered as starting point for the developement of novel and more potent anti-tubercular agents in future.